Comparison of liquid and filter sampling techniques for recovery of Bacillus spores and Escherichia coli from environmental water - Abdel-Hady, Ahmed; Monge, Mariela; Aslett, Denise; Mikelonis, Anne; Touati, Abderrahmane; Ratliff, Katherine (Journal of environmental management, 2024)
Historically, detecting water contamination has involved collecting and directly analyzing liquid samples, but recent advances in filter sampling methods offer numerous potential advantages. Emerging technologies, including environmental DNA (eDNA) samplers, could be used for remote microbial contamination sampling, but work is needed to determine if target microorganisms can be recovered from filters at comparable levels to traditional sampling methods. In this study, Escherichia coli and a surrogate for Bacillus anthracis spores were sampled from synthetic stormwater and quantified using both direct liquid and filter methods, and dwell time tests compared microorganism persistence in water and on filters. At nearly all tested timepoints, the recoveries of spores from membrane filters were within 0.5 log10 colony forming units per sample (CFU/sample) compared to the liquid-only samples, suggesting that the use of filter sampling is a feasible alternative to liquid-based sampling, and samples were held for up to 4 weeks without significant sample degradation. Recoveries for E. coli remained relatively consistent for ∼3 days in phosphate buffered saline (PBS), in synthetic stormwater, and on membrane filters, but decreases in recoveries were observed for samples held for >3 days. These results indicate that emerging water sampling technologies, which reduce logistical burdens and offer potential cost savings, can be leveraged to characterize biological contamination in water matrices with multiple types of microbiological agents. •Emerging sampling technologies are useful for monitoring water quality.•Filtration-based sampling can be used to quantify bacterial contamination in water.•Recoveries of bacteria from filters were similar to direct analysis of water.•Spore samples can be held for up to 4 weeks without sample degradation.•Cold storage improves E. coli sample recoveries at longer holding times (1–2 weeks).